Muslims and the making of modern Europe - Greble, Emily (Oxford scholarship online, 2021)
Drawing upon Muslim Europe's own voices, institutions, and experiences, this compelling work reframes the debates on European secularism, the historic role of Shari'a law in diverse European states, Muslims and Nazis, Muslims and Communists, and the contributions of Muslims to Europe today.